Emerging perspectives on osteonecrosis of the femoral head: the role of circular RNAs and long non-coding RNAs - a systematic review - Lin, Feifei; Zhou, Shicheng; Yi, Min; Wang, Qingyu (Frontiers in Genetics, 2025)
BackgroundOsteonecrosis of the femoral head (ONFH) is a prevalent and challenging orthopedic condition that often leads to hip pain and dysfunction. Long non-coding RNAs (lncRNAs) and circular RNAs (circRNAs) have emerged as potent regulators of gene expression that influence both transcriptional and post-transcriptional processes in ONFH pathogenesis. This study aimed to investigate the association between dysregulated lncRNAs and circRNAs and their functions in ONFH.MethodsWe performed a systematic literature review of PubMed, MEDLINE, and Web of Science for all publicly available data. We included papers published before 17 April 2024, to evaluate the regulatory role and differential expression of lncRNAs and circRNAs in ONFH.ResultsForty-four eligible studies were retrieved from PubMed, MEDLINE, and Web of Science, including 19 expression profiling studies, 19 gene studies, and six therapeutic studies. A total of 37 circRNAs and 42 lncRNAs were identified using quantitative real-time PCR (qRT-PCR). Dynamic changes in lncRNA and circRNA expression are associated with the proliferation and apoptosis of bone marrow stem cells (BMSCs), bone marrow endothelial cells (BMECs), and necrotic bone tissues in ONFH. CircHIPK3 and circHGF act as miRNA sponges to disrupt the osteogenic-adipogenic equilibrium, whereas lncRNA SNHG1 and GAS5 directly suppress osteogenesis. Notably, HOX transcript antisense intergenic RNA (HOTAIR), LncAABR07053481, Miat, and LINC00473 play significant roles in ameliorating the abnormal differentiation of BMSCs and could be promising therapeutic targets for ONFH.ConclusionThis systematic review discusses the current understanding of the involvement of lncRNAs and circRNAs in ONFH pathogenesis. Despite these promising findings, the limitations include heterogeneity in the study design and insufficient in vivo validation. This work consolidates ncRNA-mediated pathways in ONFH, offering novel targets for early diagnosis and RNA-based therapies, while advocating standardized multi-omics approaches in future research.